Mikrobiyolojide Güncel Konular V (Bahar) - Tunçer, Gülşah; Özmen, Cumhur; Ala Selek, Selva; Keskin Sarıtaş, Çağla; Yıldız Ergin, Merve; Yılmaz, Ezgi; Çalışkan, Ahmet; Ünal, Gözde Gülcan; Şanlı, Kamuran; Alp Göker, Eda; Gürkaynak, Pınar; Agüloğlu Bali, Elif (Academician Publishing Book DOI Portal, 2024)
-